Recent Advances in Dual PI3K/mTOR Inhibitors for Tumour Treatment - Wu, Xianbo; Xu, Yihua; Liang, Qi; Yang, Xinwei; Huang, Jianli; Wang, Jie; Zhang, Hong; Shi, Jianyou (Frontiers in Pharmacology, 2022)
The PI3K-Akt-mTOR pathway is a viable target for cancer treatment and can be used to treat various malignant tumours, including follicular lymphoma and breast cancer. Both enzymes, PI3K and mTOR, are critical in this pathway. Hence, in recent years, an array of inhibitors targeting these two targets have been studied, showing dual PI3K/mTOR inhibition compared with single targeting small molecule inhibitors. Inhibitors not only inhibit cell proliferation but also promote cell apoptosis. These inhibitors show high potency and little drug resistance even at low doses, suggesting that PI3K/mTOR inhibitors are promising cancer drugs. Herein, we summarised the recent research of PI3K/mTOR dual inhibitors—for example, structure-activity relationship, pharmacokinetics, and clinical practice, and briefly commented on them.